O programa poroduzir - Goiás e o impacto na promoção de emprego, renda e arrecadação local - Silva, Alexandre Rezende (2018)
Tax incentives are mechanisms used by governments to promote private investment, with the objective of local development. However, the fiscal waiver, promoted by the States, which benefits a first location, incites other states to adopt the same strategy, causing a tax dispute, known as fiscal war. The Brazilian literature points the State of Goiás as one of the most active in promoting development through tax exemptions. The current tax incentive policy in the State is the Produzir Program, which emphasizes on employment and income generation and on the reduction of social and regional inequalities. Similar to other programs, Produzir is also a target for praise and criticism. However, the literature has pointed out the inexistence of conclusive evidence on the impact of these programs on important variables, such as: (i) employment, (ii) income and (iii) local collection. In this way, the present work propounds to investigate the impact of fiscal incentives on the variables exposed above, analyzing data on the municipalities of Goiás, from 2005 to 2014. Was used the regression method with panel data. The results of the econometric models pointed out that the renounced ICMS revenue, through Produzir - Goiás: (i) do not affect the job creation; (ii) has an effect on the increase in average income; and (iii) does not increases the collection of local taxes. However, there is still a need to deepen this area of research in light of its importance for local development. The assessment of tax incentive programs can be hampered both by a lack of data, as the lack of standardization of information.